Game statistics and success prediction between Portuguese men’s professional basketball teams - Janeira, M. A.; Guimarães, E. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
A total of 19 basketball game statistics collected in 220 regular season (first phase) games and in 54 playoff games from the 2015-2016 Liga Portuguesa de Basquetebol (LPB) were analyzed in order to determine which indicators that best predict teams’ success (define by success percentage). A multiple regression analysis revealed that average number of defensive rebound per game and average number of 2-points shots made per game were the best predictors, explaining 96.8% of the variance in success percentage. In playoff games, the results showed that average number of defensive rebound per game was the best predictors, explaining 53.5% of the variance in success percentage. These findings reveal that in both LPB phases success it’s more associated to a defensive dimension of the game.